2007
DOI: 10.1021/jo0708846
|View full text |Cite
|
Sign up to set email alerts
|

Red Organic Light-Emitting Radical Adducts of Carbazole and Tris(2,4,6-trichlorotriphenyl)methyl Radical That Exhibit High Thermal Stability and Electrochemical Amphotericity

Abstract: Synthesis and characterization of new carbazolyl derivatives with a pendant stable radical of the TTM (tris-2,4,6-trichlorophenylmethyl radical) series are reported. The EPR spectra, electrochemical properties, absorption spectra, and luminescent properties of these radical adducts have been studied. All of them show electrochemical amphotericity being reduced and oxidized to their corresponding stable charged species. The luminescence properties of them cover the red spectral band of the emission. The lumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
140
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(170 citation statements)
references
References 27 publications
1
140
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13] Monoradicals with an S = 1/2 spin state (doublet state) are expected to exhibit highly efficient, longwavelength emission without extended p-conjugation in electroluminescent devices. [6][7][8][9][10][11][12][13] Monoradicals with an S = 1/2 spin state (doublet state) are expected to exhibit highly efficient, longwavelength emission without extended p-conjugation in electroluminescent devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13] Monoradicals with an S = 1/2 spin state (doublet state) are expected to exhibit highly efficient, longwavelength emission without extended p-conjugation in electroluminescent devices. [6][7][8][9][10][11][12][13] Monoradicals with an S = 1/2 spin state (doublet state) are expected to exhibit highly efficient, longwavelength emission without extended p-conjugation in electroluminescent devices.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because there are few examples of luminescent radicals, and radicals are not chemically stable under ambient or photoexcited conditions. [11][12][13] We prepared the luminescent (3,5-dichloro-4-pyridyl)bis(2,4,6-trichlorophenyl)methyl radical (PyBTM;F igure 1), [14] and investigated its properties and photostability upon coordinationt oA u I or Cu II or substitution with halogen atoms. [10] Lambert et al and Juliµ et al have reported the solvent-dependent luminescent properties of donor-acceptor-types table radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now,e mission from stable radicals is ar are phenomenon, and there are only three series of roomtemperature luminescent radicals:p erchlorotriphenyl methyl (PTM) radical derivatives, [13] tris(2,4,6-trichlorophenyl)methyl (TTM) radical derivatives, [14] and pyridyl-containing triarylmethyl radicals (PyBTM) (Scheme 1). [15] Because all of them have the structure of three benzene units or benzene analogues surrounding the central radical, they are catalogued into the family of triphenylmethyl radicals.…”
mentioning
confidence: 99%
“…Radical adducts 1 and 2 were prepared as already reported . Radicals 3 and 4 were synthesized by coupling the corresponding 3,6‐disubstituted carbazole derivative to the TTM radical (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we present the charge‐transport properties of a series of radical adducts based on the ambipolar [4‐( N ‐carbazolyl)‐2,6‐dichlorophenyl]bis(2,4,6‐trichlorophenyl)methyl radical (Cbz‐TTM) (Scheme ). In this series of compounds, the electron‐donating capability of the carbazole moiety, and hence, the push–pull character of the radical adducts, has been modulated by the introduction of different electron‐donating or ‐withdrawing groups on the carbazole core ( 1 , 2 ) . In addition, the extension of the conjugated π ‐system has been also considered ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%